Moisture-absorbing and antibacterial polyester fiber and method for preparing the same

CN122791504APending Publication Date: 2026-09-22HANGZHOU LINXING NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610933275.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0005]本发明解决的技术问题是:解决了涤纶纤维吸湿回潮率低、抗菌性能不佳的问题

Benefits of technology

[0025]本发明有益的技术效果:利用含有羧基和酯基的5-(偏苯三酸酐酯)间苯二甲酸的酸酐基团与微晶纤维素的羟基进行反应,得到含有大量羧基和酯基的多羧基微晶纤维素,多个羧基与Al3+等金属离子交联后,形成三维空间网络,比表面积更大,负载位点更多,与Ag+发生离子交换后,将更多的抗菌Ag+负载到纤维素基体中,显著提高了涤纶纤维的抗菌率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of fibers, and discloses a moisture-absorbing and antibacterial polyester fiber and a preparation method, wherein polyethylene terephthalate and a multi-carboxyl microcrystalline cellulose silver-loaded antibacterial agent are mixed, spinning is performed in a melt spinning machine, the fiber is stretched by a drafting machine, and is wound and collected to obtain the moisture-absorbing and antibacterial polyester fiber. + More antibacterial Ag The multi-carboxyl microcrystalline cellulose silver-loaded antibacterial agent contains a large number of hydrophilic carboxyl groups, is beneficial to improve the moisture absorption and moisture regain of the polyester fiber, contains a large number of benzoate groups, has good compatibility with the polyethylene terephthalate, has little influence on the mechanical properties of the fiber, and enables the polyester fiber to have good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber technology, specifically to a moisture-absorbing and antibacterial polyester fiber and its preparation method. Background Technology

[0002] Polyester fiber possesses high mechanical strength, elasticity, dimensional stability, and abrasion resistance, making it widely used in clothing, home textiles, and outdoor products. However, polyester fiber has low moisture absorption and regain, and poor hydrophilicity, which can lead to problems such as stuffiness, lack of breathability, and static electricity in polyester textiles. Furthermore, ordinary polyester fiber generally has limited antibacterial properties, restricting its application in medical and hygiene products.

[0003] Adding inorganic antibacterial agents, such as silver and zinc oxide, to polyester fibers can effectively improve their antibacterial properties. Among them, silver-based antibacterial agents have the advantages of strong bactericidal ability, broad-spectrum antibacterial activity, and being non-toxic and environmentally friendly. Carriers for silver-based antibacterial agents include zirconium phosphate, titanium dioxide, and chitosan.

[0004] Cellulose has excellent biocompatibility, good hydrophilicity, and is inexpensive and readily available, making it widely used in textiles and other fields. Patent CN116262989B discloses a nano-zinc oxide modified flame-retardant and antibacterial polyester fiber and its preparation method. The nano-zinc oxide-cellulose nanocrystals improve the flame-retardant and antibacterial properties of polyester fiber. However, this patent does not solve the problem of low moisture regain of polyester fiber. Summary of the Invention

[0005] The technical problem solved by this invention is to address the issues of low moisture regain and poor antibacterial properties of polyester fibers.

[0006] The technical solution of this invention is: a method for preparing moisture-absorbing and antibacterial polyester fiber:

[0007] (1) In an ice-water bath, 1,4-dioxane, pyridine, 5-hydroxyisophthalic acid, and trimellitic anhydride chloride were added to a flask. Nitrogen gas was introduced to carry out the reaction. The mixture was filtered, and the filtrate was concentrated by rotary evaporation. The product was washed with petroleum ether and then recrystallized in ethyl acetate to obtain 5-(tripteriic anhydride ester)isophthalic acid. The reaction formula is as follows:

[0008] .

[0009] (2) Add glacial acetic acid, microcrystalline cellulose, 5-(triphenyltrihydride) isophthalic acid, and sodium acetate to a flask, stir to react, cool, pour the solution into ethanol, stir, filter, wash the solid with ethanol, and dry to obtain polycarboxylated microcrystalline cellulose. The reaction formula is:

[0010] .

[0011] (3) Add water and polycarboxylated microcrystalline cellulose to the flask, stir, add an aqueous solution of metal salt to carry out ion crosslinking, filter, wash the solid with water, then add it to water, stir to disperse, add an aqueous solution of silver nitrate, stir under light to carry out ion exchange, filter, wash the solid with water, dry, and obtain the silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose.

[0012] (4) Polyethylene terephthalate and silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose are mixed and spun in a melt spinning machine. The fibers are stretched by a drawing machine, wound and collected to obtain moisture-absorbing and antibacterial polyester fibers.

[0013] Furthermore, in (1), the molar ratio of pyridine, 5-hydroxyisophthalic acid, and trimellitic anhydride acyl chloride is (1.2-1.3):1:(1-1.2).

[0014] Furthermore, in (1), the reaction temperature is 45-60℃ and the reaction time is 0.5-1h.

[0015] Furthermore, in (2), the mass ratio of microcrystalline cellulose, 5-(triphenyltrihydride) isophthalic acid, and sodium acetate is 100:(10-35) g:(2.8-10.3).

[0016] Furthermore, in (2), the reaction temperature is 75-90℃ and the reaction time is 2-4h.

[0017] Furthermore, in (3), the mass ratio of polycarboxylated microcrystalline cellulose, metal salt, and silver nitrate is 100:(45-80):(28-52).

[0018] Furthermore, the metal salts in (3) include aluminum trichloride, aluminum nitrate, ferric trichloride, and ferric nitrate.

[0019] Furthermore, in (3), the temperature for ionic crosslinking is 15-35℃ and the time is 2-3h.

[0020] Furthermore, in (4), the temperature for ion exchange is 15-35℃ and the time is 24-36h.

[0021] Furthermore, in (4), the mass ratio of polyethylene terephthalate to silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose is 100:(3-15).

[0022] Furthermore, in (4), the temperature of each zone of the melt spinning machine is 275-290℃.

[0023] Furthermore, in (4), the spinning speed is 800-1200 m / min.

[0024] Furthermore, in (4), the stretching ratio of the stretching machine is 3.2-3.8 times.

[0025] The beneficial technical effects of this invention are as follows: By reacting the anhydride groups of 5-(triphenyltriglyceride) isophthalic acid containing carboxyl and ester groups with the hydroxyl groups of microcrystalline cellulose, a polycarboxylated microcrystalline cellulose containing a large number of carboxyl and ester groups is obtained. Multiple carboxyl groups react with Al... 3+ After cross-linking with metal ions, a three-dimensional network is formed, resulting in a larger specific surface area and more loading sites, which interacts with Ag. + After ion exchange, more antibacterial Ag will be released. + Loading it into the cellulose matrix significantly improves the antibacterial rate of polyester fibers.

[0026] The silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose of the present invention contains a large number of hydrophilic carboxyl groups, which is beneficial to improving the moisture absorption and moisture regain of polyester fibers.

[0027] The silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose of the present invention contains a large number of benzoic acid ester groups, which improves the compatibility with polyethylene terephthalate and has little impact on the mechanical properties of the fiber, thus giving polyester fiber good mechanical properties. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of this application clearer, a further detailed description of this application is provided below. The terminology used in the following embodiments is for the purpose of describing specific embodiments only and is not intended to be limiting of this application.

[0029] The following polyethylene terephthalate (PET) powder was purchased from Shenzhen Wansuyuan Rubber & Plastics Co., Ltd. The microcrystalline cellulose (MCC) was purchased from Jiangsu Aofu Biotechnology Co., Ltd. The carboxymethyl cellulose (CMC FH9) was also purchased from Jiangsu Aofu Biotechnology Co., Ltd.

[0030] Example 1 (1) In an ice-water bath, pyridine, 5-hydroxyisophthalic acid (the concentration of 5-hydroxyisophthalic acid in the solution was controlled to be 0.9 mol / L), trimellitic anhydride acyl chloride, 1,4-dioxane, in a molar ratio of 1.2:1:1.2, were added to a flask, nitrogen gas was introduced, the mixture was heated to 50°C, stirred for 1 h, filtered, the filtrate was concentrated by rotary evaporation, the product was washed with petroleum ether, and then recrystallized in ethyl acetate to obtain 5-(tripteriocitrate)isophthalic acid.

[0031] (2) Add glacial acetic acid, 100 parts by weight of microcrystalline cellulose (controlling the mass fraction of microcrystalline cellulose in the solution to 15%), 10 parts by weight of 5-(triphenyltrihydric anhydride) isophthalic acid, and 2.8 parts by weight of sodium acetate to a flask, heat to 90°C, stir and react for 2 hours, cool and pour the solution into ethanol, stir and filter, wash the solid with ethanol, dry and obtain polycarboxylated microcrystalline cellulose.

[0032] (3) Add water and 100 parts by weight of polycarboxylated microcrystalline cellulose (control the mass fraction of polycarboxylated microcrystalline cellulose in the solution to 2%) to the flask, stir, and then add an aqueous solution containing 45 parts by weight of aluminum trichloride (mass fraction of 20%). Perform ion crosslinking at 20°C for 3 hours. After filtration, wash the solid with water, then add it to water, stir and disperse, and add an aqueous solution containing 28 parts by weight of silver nitrate (mass fraction of 25%). Perform ion exchange at 20°C in the dark for 24 hours, stir, filter, wash the solid with water, and dry to obtain the silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose.

[0033] (4) Mix 100 parts by weight of polyethylene terephthalate and 3 parts by weight of silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose, and spin them in a melt spinning machine. The temperatures of zones 1-4 are 275℃, 290℃, 290℃ and 280℃, and the spinning speed is 1000m / min. The fiber is stretched by a drawing machine with a stretching ratio of 3.8 times, wound and collected to obtain moisture-absorbing and antibacterial polyester fiber.

[0034] Example 2 (1) In an ice-water bath, pyridine, 5-hydroxyisophthalic acid (the concentration of 5-hydroxyisophthalic acid in the solution was controlled to be 0.9 mol / L), trimellitic anhydride acyl chloride, 1,4-dioxane, in a molar ratio of 1.3:1:1, were added to a flask, nitrogen gas was introduced, the mixture was heated to 45°C, stirred for 1 h, filtered, the filtrate was concentrated by rotary evaporation, the product was washed with petroleum ether, and then recrystallized in ethyl acetate to obtain 5-(tripteriocitrate)isophthalic acid.

[0035] (2) Add glacial acetic acid, 100 parts by weight of microcrystalline cellulose (controlling the mass fraction of microcrystalline cellulose in the solution to 10%), 23 parts by weight of 5-(triphenyltrihydric anhydride) isophthalic acid, and 6.6 parts by weight of sodium acetate to a flask, heat to 75°C, stir and react for 4 hours, cool and pour the solution into ethanol, stir and filter, wash the solid with ethanol, dry, and obtain polycarboxylated microcrystalline cellulose.

[0036] (3) Add water and 100 parts by weight of polycarboxylated microcrystalline cellulose (control the mass fraction of polycarboxylated microcrystalline cellulose in the solution to 1.5%) to the flask, stir, and then add an aqueous solution containing 65 parts by weight of aluminum trichloride (mass fraction of 20%). Perform ion crosslinking at 25°C for 2 hours. After filtration, wash the solid with water, then add it to water, stir and disperse, and add an aqueous solution containing 42 parts by weight of silver nitrate (mass fraction of 25%). Perform ion exchange at 25°C in the dark for 36 hours, stir, filter, wash the solid with water, and dry to obtain the silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose.

[0037] (4) Mix 100 parts by weight of polyethylene terephthalate and 9 parts by weight of silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose, and spin them in a melt spinning machine. The temperatures of zones 1-4 are 275℃, 290℃, 290℃ and 280℃, and the spinning speed is 1200m / min. The fiber is stretched by a drawing machine with a stretching ratio of 3.8 times, wound and collected to obtain moisture-absorbing and antibacterial polyester fiber.

[0038] Example 3 (1) In an ice-water bath, pyridine, 5-hydroxyisophthalic acid (the concentration of 5-hydroxyisophthalic acid in the solution was controlled to be 0.8 mol / L), trimellitic anhydride acyl chloride, 1,4-dioxane, in a molar ratio of 1.2:1:1.2, were added to a flask, nitrogen gas was introduced, the mixture was heated to 60°C, stirred for 0.5 h, filtered, the filtrate was concentrated by rotary evaporation, the product was washed with petroleum ether, and then recrystallized in ethyl acetate to obtain 5-(tripteriocitrate)isophthalic acid.

[0039] (2) Add glacial acetic acid, 100 parts by weight of microcrystalline cellulose (controlling the mass fraction of microcrystalline cellulose in the solution to 15%), 35 parts by weight of 5-(triphenyltrihydric anhydride) isophthalic acid, and 10.3 parts by weight of sodium acetate to a flask, heat to 80°C, stir and react for 4 hours, cool and pour the solution into ethanol, stir and filter, wash the solid with ethanol, dry, and obtain polycarboxylated microcrystalline cellulose.

[0040] (3) Add water and 100 parts by weight of polycarboxylated microcrystalline cellulose (control the mass fraction of polycarboxylated microcrystalline cellulose in the solution to 2%) to the flask, stir, and then add an aqueous solution containing 80 parts by weight of aluminum trichloride (mass fraction of 20%). Perform ion crosslinking at 20°C for 3 hours. After filtration, wash the solid with water, then add it to water, stir and disperse, and add an aqueous solution containing 52 parts by weight of silver nitrate (mass fraction of 30%). Perform ion exchange at 20°C in the dark for 36 hours, stir, filter, wash the solid with water, and dry to obtain the silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose.

[0041] (4) Mix 100 parts by weight of polyethylene terephthalate and 15 parts by weight of silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose, and spin them in a melt spinning machine. The temperatures of zones 1-4 are 275℃, 290℃, 290℃ and 280℃, and the spinning speed is 800m / min. The fiber is stretched by a drawing machine with a stretching ratio of 3.2 times, wound and collected to obtain moisture-absorbing and antibacterial polyester fiber.

[0042] Comparative Example 1 (1) 100 parts by weight of polyethylene terephthalate were spun in a melt spinning machine. The temperatures of zones 1-4 were 275℃, 290℃, 290℃, and 280℃, and the spinning speed was 1000 m / min. The fibers were stretched by a drawing machine with a stretching ratio of 3.8 times, wound and collected to obtain polyester fibers.

[0043] Comparative Example 2 (1) Polycarboxylated microcrystalline cellulose was prepared according to the method of Example 1.

[0044] (2) Add water and 100 parts by weight of polycarboxylated microcrystalline cellulose (control the mass fraction of polycarboxylated microcrystalline cellulose in the solution to 2%) to the flask, stir, and then add an aqueous solution containing 28 parts by weight of silver nitrate (mass fraction of 25%). Stir and carry out ion exchange for 24 hours at 20°C in the dark. After filtration, wash the solid with water and dry to obtain the silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose.

[0045] (3) Mix 100 parts by weight of polyethylene terephthalate and 3 parts by weight of silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose, and spin them in a melt spinning machine. The temperatures of zones 1-4 are 275℃, 290℃, 290℃ and 280℃, and the spinning speed is 1000m / min. The fibers are stretched by a drawing machine with a stretching ratio of 3.8 times, wound and collected to obtain polyester fibers.

[0046] Comparative Example 3 (1) Add glacial acetic acid, 100 parts by weight of microcrystalline cellulose (controlling the mass fraction of microcrystalline cellulose in the solution to 15%), 10 parts by weight of phthalic anhydride, and 2.8 parts by weight of sodium acetate to a flask, heat to 90°C, stir and react for 2 hours, cool and pour the solution into ethanol, stir and filter, wash the solid with ethanol, dry, and obtain phthalic anhydride ester microcrystalline cellulose.

[0047] (2) Add water and 100 parts by weight of phthalic anhydride ester microcrystalline cellulose (control the mass fraction of polycarboxylated microcrystalline cellulose in the solution to 2%) to a flask, stir, and then add an aqueous solution containing 45 parts by weight of aluminum trichloride (mass fraction of 20%). Perform ion crosslinking at 20°C for 3 hours. After filtration, wash the solid with water, then add it to water, stir and disperse, and add an aqueous solution containing 28 parts by weight of silver nitrate (mass fraction of 25%). Perform ion exchange at 20°C in the dark for 24 hours, stir, filter, wash the solid with water, and dry to obtain silver-loaded microcrystalline cellulose antibacterial agent.

[0048] (3) Mix 100 parts by weight of polyethylene terephthalate and 3 parts by weight of silver-loaded microcrystalline cellulose antibacterial agent, and spin them in a melt spinning machine. The temperatures of zones 1-4 are 275℃, 290℃, 290℃ and 280℃, and the spinning speed is 1000m / min. The fibers are stretched by a drawing machine with a stretching ratio of 3.8 times, wound and collected to obtain polyester fibers.

[0049] Comparative Example 4 (1) Water and 100 parts by weight of carboxymethyl cellulose were added to a flask. After stirring, an aqueous solution containing 45 parts by weight of aluminum trichloride (mass fraction of 20%) was added. Ionic crosslinking was carried out at 20°C for 3 hours. After filtration, the solid was washed with water and then added to water. The mixture was stirred and dispersed. An aqueous solution containing 28 parts by weight of silver nitrate (mass fraction of 25%) was added. Ion exchange was carried out at 20°C in the dark for 24 hours. After filtration, the solid was washed with water and dried to obtain silver-loaded antibacterial agent of carboxymethyl cellulose.

[0050] (2) Mix 100 parts by weight of polyethylene terephthalate and 3 parts by weight of carboxymethyl cellulose silver-loaded antibacterial agent, and spin them in a melt spinning machine. The temperatures of zones 1-4 are 275℃, 290℃, 290℃ and 280℃, and the spinning speed is 1000m / min. The fibers are stretched by a drawing machine with a stretching ratio of 3.8 times, wound and collected to obtain polyester fibers.

[0051] Table 1 Properties of polyester fiber

[0052]

[0053] Examples 1-3 involve melt spinning a blend of polyethylene terephthalate (PET) and polycarboxylated microcrystalline cellulose loaded with silver antibacterial agent. The resulting polyester fibers exhibit higher moisture regain and antibacterial activity while maintaining good breaking strength and elongation at break. This is primarily because the microcrystalline cellulose introduces a large number of hydrophilic carboxyl groups, which improves the hygroscopicity and moisture regain of the polyester fibers, significantly exceeding those of Comparative Example 1. Furthermore, the microcrystalline cellulose undergoes Al... 3+ After cross-linking with metal ions, a three-dimensional network is formed, resulting in a larger specific surface area and more loading sites, which interacts with Ag. + After ion exchange, more antibacterial Ag will be released. + Loading it into the cellulose matrix significantly improves the antibacterial rate of polyester fibers. Meanwhile, the silver-loaded antibacterial agent in polycarboxylated microcrystalline cellulose contains a large number of benzoate groups (…). The improved compatibility with polyethylene terephthalate (PET) has minimal impact on the mechanical properties of the fiber, giving polyester fibers good mechanical properties.

[0054] The difference between Comparative Example 2 and Example 1 is that aluminum trichloride was not added for ionic crosslinking. The polycarboxylated microcrystalline cellulose did not crosslink to form a three-dimensional network, resulting in fewer loading sites and reduced resistance to Ag. + The adsorption loading effect is poor, and most of the Ag... + Removed by washing, resulting in Ag in the antibacterial agent + The content is very low, and the antibacterial rate of polyester fiber is low.

[0055] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3, which uses phthalic anhydride for esterification, results in phthalic anhydride ester microcrystalline cellulose with lower carboxyl group content, fewer ionic crosslinking sites, and a less effective three-dimensional network. This also affects the Ag... + The load-bearing effect is poor, the antibacterial rate of polyester fiber is low, and the carboxyl content of phthalic anhydride ester microcrystalline cellulose is low. The moisture regain of polyester fiber is low, and the ester content is low. It is not compatible with polyethylene terephthalate, and the breaking strength and breaking elongation of polyester fiber are low.

[0056] The difference between Comparative Example 4 and Example 1 is that conventional carboxymethyl cellulose was used instead of polycarboxylated microcrystalline cellulose silver-loaded antibacterial agent. The moisture regain and antibacterial rate of the polyester fiber prepared were significantly lower than those of Example 1. At the same time, carboxymethyl cellulose does not contain a large number of ester groups, which is very poor with polyethylene terephthalate and has a significant impact on the mechanical properties of polyester fiber, resulting in very low breaking strength and breaking elongation.

[0057] The above description is merely a preferred embodiment of the present invention and the technical principles employed. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and various obvious changes, readjustments, and substitutions can be made without departing from the scope of protection of the present invention.

Claims

1. A method for preparing moisture-absorbing and antibacterial polyester fiber, characterized in that, The preparation method includes: S1. Add glacial acetic acid, microcrystalline cellulose, 5-(triphenyltrihydride) isophthalic acid, and sodium acetate to a flask, stir to react, cool, pour the solution into ethanol, stir, filter, wash the solid, and dry to obtain polycarboxylated microcrystalline cellulose. S2. Add water and polycarboxylated microcrystalline cellulose to a flask, stir, add an aqueous solution of metal salt to carry out ionic cross-linking, filter and wash the solid, then add it to water, stir to disperse, add an aqueous solution of silver nitrate, stir under the dark to carry out ion exchange, filter and wash the solid, dry to obtain silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose. S3. Polyethylene terephthalate and silver-loaded antibacterial agent of polycarboxylated microcrystalline cellulose are mixed and spun in a melt spinning machine. The fibers are stretched by a drawing machine, wound and collected to obtain moisture-absorbing and antibacterial polyester fibers.

2. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 1, characterized in that, The mass ratio of microcrystalline cellulose, 5-(triphenyltriglyceride) isophthalic acid, and sodium acetate in S1 is 100:(10-35) g:(2.8-10.3).

3. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 1, characterized in that, The reaction temperature in S1 is 75-90℃, and the reaction time is 2-4h.

4. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 1, characterized in that, The mass ratio of polycarboxylated microcrystalline cellulose, metal salt, and silver nitrate in S2 is 100:(45-80):(28-52).

5. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 4, characterized in that, The metal salt is any one or a combination of aluminum trichloride, aluminum nitrate, ferric trichloride, and ferric nitrate.

6. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 1, characterized in that, The temperature for ion crosslinking in S2 is 15-35℃ and the time is 2-3h; the temperature for ion exchange is 15-35℃ and the time is 24-36h.

7. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 1, characterized in that, The mass ratio of polyethylene terephthalate and silver-loaded antibacterial agent in S3 is 100:(3-15).

8. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 1, characterized in that, The temperature of each zone of the melt spinning machine in S3 is 275-290℃, the spinning speed is 800-1200m / min, and the stretching ratio of the drawing machine is 3.2-3.8 times.

9. The method for preparing moisture-absorbing and antibacterial polyester fiber according to claim 1, characterized in that, The preparation method of 5-(triphenyltriacrylic anhydride ester) isophthalic acid is as follows: In an ice-water bath, pyridine, 5-hydroxyisophthalic acid, and trimellitic anhydride acyl chloride of 1,4-dioxane in a molar ratio of (1.2-1.3):1:(1-1.2) are added to a flask, nitrogen gas is introduced, the mixture is heated to 45-60℃, and the reaction is stirred for 0.5-1h. The mixture is filtered, the filtrate is concentrated by rotary evaporation, the product is washed, and then recrystallized to obtain 5-(triphenyltriacrylic anhydride ester) isophthalic acid.

10. A moisture-absorbing and antibacterial polyester fiber obtained by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • A kind of nano zinc oxide modified flame retardant antibacterial polyester fiber and preparation method thereof

    CN116262989B